2017
DOI: 10.1111/birt.12294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise‐based interventions on postpartum depression: A meta‐analysis of randomized controlled trials

Abstract: Physical exercise during pregnancy and the postpartum period is a safe strategy to achieve better psychological well-being and to reduce postpartum depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 41 publications
9
100
1
8
Order By: Relevance
“…Besides, the American College of Obstetricians and Gynaecologists (2002) recommends that all adults (including pregnant and postpartum women without complications) should participate in at least 30 minutes of moderate-intensity physical activity on most days of the week. Additionally, it has been suggested that exercise is as successful as antidepressants in the treatment of major clinical depression (Blumenthal et al, 2007;Poyatos-León et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the American College of Obstetricians and Gynaecologists (2002) recommends that all adults (including pregnant and postpartum women without complications) should participate in at least 30 minutes of moderate-intensity physical activity on most days of the week. Additionally, it has been suggested that exercise is as successful as antidepressants in the treatment of major clinical depression (Blumenthal et al, 2007;Poyatos-León et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 The presence of polyunsaturated fatty acids, prostaglandin J 2, and adipokines in breast milk may explain these compensatory mechanisms, although more robust conclusions are needed. 49 Another pathway that might explain the relationship between breastfeeding and CRF in children and adolescents is maternal CRF, not only because of genetics pathways, 51,52 but also because good CRF levels in mothers have been associated with lower postpartum depression scores, 53 and postpartum depression is a risk factor for early breastfeeding cessation. 54 However, further research on the pathophysiological mechanisms driving the relationship between breastfeeding and CRF is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, gestational depression negatively influences early psychological development, and mothers’ anxiety and psychological wellbeing are related to mothers’ physical activity patterns and children's behaviour . As physical activity during pregnancy has been demonstrated as a safe strategy against postpartum depression, its influence in children's neurodevelopment and behaviour does not seem unreasonable. Conversely, sedentary behaviour may increase the risk of depression and anxiety disorders during pregnancy, and mothers’ depression has been associated with poorer child behaviour and psychological development …”
Section: Factors Related To Children's Neurodevelopmentmentioning
confidence: 99%
“…Research has shown that physical activity during pregnancy could have a positive effect on neonatal and maternal outcomes, such as gestational age, Apgar score, gestational diabetes, maternal weight gain and type of delivery . Furthermore, physical activity has been related to a lower incidence and better management of postpartum depression and mood, as well as with better scores in offspring's cognition variables, academic achievement and classroom behaviours …”
Section: Introductionmentioning
confidence: 99%